A Role for GDNF and Soluble APP as Biomarkers of Amyotrophic Lateral Sclerosis Pathophysiology - Stanga, Serena; Brambilla, Liliana; Tasiaux, Bernadette; Dang, Anh H.; Ivanoiu, Adrian; Octave, Jean-Noël; Rossi, Daniela; van Pesch, Vincent; Kienlen-Campard, Pascal (Frontiers in Neurology, 2018)
The current inability of clinical criteria to accurately identify the “at-risk group” for Amyotrophic Lateral Sclerosis (ALS) development as well as its unknown etiology are fueling the interest in biomarkers aimed at completing clinical approaches for the diagnosis. The Glial cell line-derived neurotrophic factor (GDNF) is a diffusible peptide critically involved in neuronal differentiation and survival. GDNF is largely studied in various neurological and neuromuscular diseases, with a great interest in the peripheral nervous system (PNS). The recent discovery of Amyloid Precursor Protein (APP)-dependent GDNF regulation driving neuro-muscular junctions’ formation in APP null transgenic mice, prompts to study whether neurodegeneration relies on loss or gain of APP function and suggests that it could affect peripheral processes. Here, we explored a brand-new aspect of the loss of trophic support in ALS by measuring GDNF, APP, soluble APP fragments and Aβ peptides levels in SOD1WT or SOD1G93A transgenic mouse models of ALS and in human biological fluids (i.e. serum and cerebrospinal fluid (CSF)) from ALS patients and control subjects. Our results show that both GDNF and soluble APP fragments levels are altered at the onset of motor deficits in mice and that their levels are also modified in patient samples. This study indicates that both GDNF and soluble APPα represent possible biomarkers for ALS.